2014
DOI: 10.1111/mec.12732
|View full text |Cite
|
Sign up to set email alerts
|

Island bat diets: does it matter more who you are or where you live?

Abstract: Differences in body size, echolocation call frequency and location may result in diet partitioning among bat species. Comparisons between island populations are one way to evaluate these competing hypotheses. We conducted a species-level diet analysis of three Rhinolophus and one Hipposideros species on the Philippine islands of Cebu, Bohol and Siquijor. We identified 655 prey (MOTUs) in the guano from 77 individual bats. There was a high degree of overlap among species' diets despite differences in body size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 56 publications
3
28
1
1
Order By: Relevance
“…Similarly, Sedlock et al . () also found interspecific dietary overlap and concluded that location determined what bats consume more effectively than their taxonomy or perceptual abilities. Here, we suggest that seasonal changes in food abundance have the same effect.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Similarly, Sedlock et al . () also found interspecific dietary overlap and concluded that location determined what bats consume more effectively than their taxonomy or perceptual abilities. Here, we suggest that seasonal changes in food abundance have the same effect.…”
Section: Discussionmentioning
confidence: 95%
“…; Sedlock et al . ). However, we found no evidence that diet changes in the same direction as insect abundance/diversity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…DNA-based techniques have been used to identify prey species in the diet of insectivorous bats (Clare et al 2009(Clare et al , 2011Bohmann et al 2011;Razgour et al 2011;Zeale et al 2011;Dodd et al 2012;Burgar et al 2014;Sedlock et al 2014). Carter et al (2006) reported on techniques for isolation, amplification, and identification of avian DNA from fecal samples of Diaemus youngi, the white-winged vampire bat, a specialist avian sanguinivore (Greenhall et al 1983).…”
mentioning
confidence: 99%